Growth of Local Sengon (Paraserianthes falcataria (L.) Nielsen) and Productivity of Upland Rice (Oryza sativa L.) Inpago LIPI Go2 Variety in Agroforestry Systems - Nurheni Wijayanto; Nurhayati Nurhayati (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2022)
Sengon (Paraserianthes falcataria (L.) Nielsen) is a fast-growing and widely cultivated species in Indonesia. In addition, sengon is a type that is easy to adapt to the environmental conditions in which it grows. Upland rice (Oryza sativa L.) is a type of rice that is tolerant to drought. Sengon and upland rice in agroforestry can be an alternative in more effective land use. This study aims to measure local sengon growth, determine the productivity of upland rice in Inpago LIPI Go2 variety and light intensity in the sengon 1.5 m x 1.5 m and 1.5 m x 3 m line planting in agroforestry systems. Data analysis was performed by testing variance at the level of 0.05% and if the treatment had a significant effect, it was tested further using the Tukey Test. The results of this study indicate that sengon in the 6 months after planting is not affected by pathway treatment, but line planting treatment has a significant effect on upland rice productivity results. Beside age factor of sengon, it can be several other factors such as pest and disease attacks on sengon or upland rice. Keywords: agroforestry, light intensity, sengon, upland rice